Loss of heterozygosity of essential genes represents a widespread class of potential cancer vulnerabilities - Caitlin A. Nichols (Nature Portfolio, 2020)
In tumors, hundreds of genes can undergo loss of heterozygosity (LOH). Here, the authors investigate the potential for this LOH as a class of non-driver cancer vulnerabilities.